Contriving a catalytically active structure from an inert conformation: a density functionalinvestigation of Al, Hf, and Ge doping of Au-20 tetrahedral clusters - Manzoor, Dar; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2016)
The transformation of an inert structure into a catalytically active conformation has immense potential from a structural engineering point of view. In the present work, we explored methods of achieving such a transformation through a density-functional-based study. Au-20 is known be one of the most stable and catalytically inert gold clusters, with a well-known tetrahedral structure. We demonstrate the transformation of the inert Au-20 conformation into a highly active catalytic cluster through selective doping with Hf and Ge atoms. Depending on the dopant, the inert tetrahedral Au-20 cluster evolves into either an endohedral or a hollow-cage-like conformation. The structural changes are manifested in the catalytic properties as well, with the result that the transformed doped cages exhibit extremely low activation barriers for the environmentally important CO oxidation reaction as compared to reported inert Au-20 cluster. The activation barriers for CO oxidation are particularly low (<0.12 eV) when germanium is directly involved in the CO oxidation. Thus, the current work highlights the importance of engineering structural properties of metal nanoclusters with the help of heteroatom dopants for future applications in efficient catalysis.